Analisis Hubungan Semangat kerja dan Kepuasan Kerja Terhadap Kinerja Guru: Study Kasus di SMK Darul Hikmah Malang - Dita Rachmawati; Ayu Rachmawaty; Lailatul Mahmudah (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2022)
This research was aimed at identifying the effects of an analysis of the relationship between work enthusiasm and job satisfaction with teacher performance In reality of the work done, the atmosphere of the work environment is not conducive, such as with colleagues who do not support each other, the leader's policy being less supportive, and students whose actions are taken. On the other hand, there are some of them who lose their enthusiasm to teach, feel bored, and are saturated with work. Shows the lackluster organizational climate that affects teacher performance. School performance is determined by the atmosphere or climate of the working environment in the school. In developed countries, research on the working climate in schools (school working environment or school climate) has developed well and made a significant contribution to the formation of effective schools.